2014
DOI: 10.1007/s00702-014-1251-x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of serotonin-induced itch responses by inhibition of endocannabinoid degradative enzymes, fatty acid amide hydrolase and monoacylglycerol lipase

Abstract: Itch and pain are two irritating sensations sharing a lot in common. Considering the antinociceptive effects of blockade of endocannabinoid degrading enzymes in pain states, we attempted to reduce scratching behavior by endocannabinoid modulation, i.e. by inhibiting fatty acid amide hydrolase (FAAH), monoacylglycerol lipase (MAGL), or cellular uptake of endocannabinoids. Scratching behavior was induced by intradermal injection of serotonin to Balb/c mice. URB597 (10 mg/kg, i.p.), a FAAH inhibitor, JZL184 (16 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Cannabinoid receptor agonists have a tendency to attenuate scratching behaviour in mice, whereas CB1 receptors mediate rimonabant‐induced pruritic behaviour . Modulation of itch sensation by augmenting the endocannabinoid anandamide (2‐arachidonylglycerol) tonus through inhibition of the endocannabinoid catabolic enzymes (fatty acid amide hydrolase, monoacylglycerol lipase) also appears to be a promising target for treating pruritus . In line with these previous studies, we found that serotonin‐induced scratching behaviour was dose‐dependently suppressed by the cannabinoid agonist WIN 55,212‐2.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Cannabinoid receptor agonists have a tendency to attenuate scratching behaviour in mice, whereas CB1 receptors mediate rimonabant‐induced pruritic behaviour . Modulation of itch sensation by augmenting the endocannabinoid anandamide (2‐arachidonylglycerol) tonus through inhibition of the endocannabinoid catabolic enzymes (fatty acid amide hydrolase, monoacylglycerol lipase) also appears to be a promising target for treating pruritus . In line with these previous studies, we found that serotonin‐induced scratching behaviour was dose‐dependently suppressed by the cannabinoid agonist WIN 55,212‐2.…”
Section: Discussionsupporting
confidence: 86%
“…Scratching of the injection region by the hind paws was regarded as spontaneous scratching. The mice typically scratched several times per second, with such reaction accepted as one bout of scratching …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of URB597 (and the reduced behaviour in the FAAH þ/þ mice) was blocked by rimonabant (Schlosburg et al 2009). Scratching behaviour in mice and rats following intradermal serotonin administration into the rostral part of the back is reduced by both URB597 and JZL184 Tosun et al 2014). In contrast, the two compounds increased, rather than decreased, the scratching behaviour following serotonin injection into the cheek of the rats ).…”
Section: Painmentioning
confidence: 91%